Square-wave voltammetric trace determination of aminophylline in urine – application for pharmaceutical formulation - M. M. Al-Imam; S. T. Sulaiman (Хімія, фізика та технологія поверхні, 2015)
The voltammetric properties of pure aminophylline have been studied by a direct method in the aqueous solution. The substance has revealed a clear and major reduction peak at potential –0.622 V against the reference electrode (Ag/AgCl/sat. KCl).The calibration curve of aminophylline in the ammonium buffer (NH3/NH4Cl, pH = 10.0) has been studied under optimum conditions. The relationship has been linearized within the scope of molar concentration (1.09·10-6–2.107·10?5). The correlation coefficient is R = 0.9903. The calibration curve has been also studied in the presence of human urine. The standard addition method was used successfully to determine the drug in urine of the patients as well as for the analysis of drug in the tablets, and compared with standard method